The dragon from Chicago : the untold story of an American reporter in Nazi Germany - Toler, Pamela D. (Beacon Press, 2024)
"A captivating look at Sigrid Schultz--one of the earliest reporters to warn Americans of the rising threat of the Nazi regime"--